Watercolour flowers for the absolute beginner - Peart, Fiona (Absolute beginner., 2023)
Flowers are a perennial favourite of artists; and what better medium than luminous, delicate watercolour? Fiona Peart's new book is a complete course in learning to paint flowers, packed with handy hints and tips for new artists - or indeed anyone who wants to capture the beauty of flowers with paint. Numerous simple step-by-step exercises are seeded through the book to allow the reader's skills to grow towards more complex and rewarding projects. A range of flowers are included, from hydrangeas to camellias to hellebores. Fiona's clear, down-to-earth and friendly instructions encourage the reader to try different styles, while the 21 full-size, traceable outlines included mean that even those who don't wish to draw can get started quickly and simply, following the instructions provided.